SHAPING THE FUTURE IN THE MANAGEMENT AND SOLUTION OF SOCIAL PROBLEMS: SOCIAL ENTREPRENEUR COOPERATIVES AND THE EXAMPLE OF ENTERPRISE EUROPE NETWORK (Third Sector Social Economic Review, 2017)
Dealing with the challenging issues of globalisation in the production and sharing it is no longer in the foreground the topic that attracts attention of the entire organization is shared with an increasing interest in social entrepreneurship. In the most basic sense Social entrepreneurship is promoting social change and creating economic and social value by accepting the reduction of social problems as an exit point. At the same time,it is finding innovative solutions to the problems of disadvantaged groups that the state and private sector can not reach, neglected, excluded from society. European Entrepreneurship Network has been established in Europe to combine social entrepreneurial developments, especially with cooperatives, to establish social economic ties among them and to provide opportunities for economic development through social economic networks. The Enterprise Europe Network is the largest network in the world, with more than 3,000 employees working in more than 60 countries in more than 60 countries, especially with SMEs who want to establish international cooperation, as well as with large firms and researchers. This economic social network is to support trade and industry chambers, technology transfer centers, foundations, associations, cooperatives, research centers and SMEs.In this study, the characteristics of the social entrepreneurial cooperative as the developing face of the cooperative in the future and the role of the social problem in the solution will be explained.
Keywords: Entrepreneurship; Social entrepreneurship; Cooperatives; Social entrepreneur cooperatives; Social economic network; The European entrepreneurship network.